Endoscopic submucosal dissection for early esophageal cancer in elderly patients with relative indications for endoscopic treatment - Qi, Zhi-Peng; Chen, Tao; Li, Bing; Ren, Zhong; Yao, Li-Qing; Shi, Qiang; Cai, Shi-Lun; Zhong, Yun-Shi; Zhou, Ping-Hong (Endoscopy, 2018)
Background According to the Japanese Esophageal Society (JES) guidelines, early esophageal squamous cell carcinoma (SCC) involving the muscularis mucosae (M3) or upper submucosal (SM1) layers are relative indications for endoscopic submucosal dissection (ESD). Additional esophagectomy or chemoradiotherapy is recommended for patients with relative indications after evaluation. However, elderly patients (≥ 60 years) with relative indications in China often refuse additional treatment because of the debilitating side effects. The aim of this study was to evaluate the long-term outcomes of elderly patients with relative indications who did not undergo additional treatment after ESD.Methods Data from elderly patients with relative indications who underwent ESD for early esophageal SCC between January 2008 and December 2013 were reviewed retrospectively. Stricture and recurrence, and 5-year progression-free survival (PFS) and overall survival rates were compared with patients with absolute indications for ESD.Results 158 elderly patients were included and analyzed (89 in the absolute indications group and 69 in the relative indications group). The baseline characteristics were balanced between the two groups. During 56 months (range 1 – 108) of follow-up, the postoperative stricture rates were similar in the absolute and relative indications groups (21.3 % vs. 31.9 %; P  = 0.13). The hazard ratio (HR) for PFS in the absolute vs. the relative indications groups was 1.025 (95 % confidence interval [CI] 0.36 – 2.95; P = 0.96). The 5-year PFS rates were 90.5 % (95 %CI 83.44 – 97.56) and 90.8 % (95 %CI 83.74 – 97.86) for the absolute and relative indications groups, respectively. The HR for overall survival in the absolute vs. the relative indications groups was 0.564 (95 %CI 0.13 – 2.52; P = 0.45). The 5-year overall survival rates were 96.6 % (95 %CI 92.88 – 100) and 95.6 % (95 %CI 90.70 – 100) for the absolute and relative indications groups, respectively.Conclusions Based on this study, regular follow-up without additional treatment may be considered as another choice for elderly patients with early esophageal SCC and relative indications after ESD.